Enhancement of thermal stability and corrosion resistance of palm oil lubricants using nonylphenol and polyethylene glycol additives - Haris Puspito Buwono; Aquilla Elka Ananda Kirana (Jurnal Polimesin, 2026)
Palm oil offers advantages as a lubricant due to its eco-friendliness, renewability, high viscosity index, good boundary lubrication properties, and compatibility with additives. However, palm oil is not very resistant to high-temperature changes, which limit its application in vehicle lubricants. This research aims to overcome the weaknesses of palm oil as a vehicle lubricant by adding Nonylphenol and Polyethylene Glycol surfactants at varying concentrations and evaluate thermal stability, engine operating temperature, and corrosion resistance.  The quantitative experiments were conducted with palm oil blend of nonylphenol surfactant and polyethylene glycol. Formulations containing 2.5%, 5%, and 7.5% surfactant concentrations were evaluated through oven-based thermal stability testing and copper strip corrosion testing according to ASTM D4048 to determine the sulfur content in lubricating oils. From the test results, palm oil-based lubricant blends containing Nonylphenol (2.5% and 5%) and Polyethylene Glycol (PEG) (2.5% and 5%) showed a corrosion classification value of 1a, the best rating in the ASTM Copper Strip Corrosion Standard. The best engine temperature test was palm-oil-based with 5% Nonylphenol.